Racial stratification and multiple outcomes in police stops and searches - Ariel, Barak (Policing and society, 2018)
The present study explores ethnic differences in stop-and-search outcomes. It uses data from 53,858 stop-and-search incidents recorded by a United Kingdom police force. Prior studies often focused on single outcomes – notably, arrests – and based on a binary majority-versus-minority categorisation of ethnicity/race. Our analysis departs from this approach by examining multiple outcomes across different ethnic groups. Focusing first on the binary categorisation, we found that stops-and-searches involving minorities were more likely to lead to arrests or to informal advice by officers than Whites, but less likely to receive formal warnings. No differences emerged in terms of encounters that resulted in ‘no further action’. However, there was no consistent pattern across any of the outcomes once the minority group was disaggregated into specific ethnic groups, despite having sufficient statistical power. Furthermore, a multivariate analysis shows that while ethnicity predicts stop-and-search outcomes, its effect is subsidiary to gender, criminal history, whether the encounter happened in a crime hotspot or not, and whether property was found during the encounter. Implications for future research are discussed.